Plasma Electrolytic Oxidation Synthesis of Heterostructured TiO2/CuxO Films for Photoelectrochemical Water Splitting Applications - Levinas, R.; Pakstas, V.; Selskis, A.; Murauskas, T.; Viter, R.; Anspoks, Andris; Pudza, Inga; Kuzmin, Alexei; Tamasauskaite-Tamasiunaite, L; Cesiulis, H.; Norkus, E. (The Electrocemical Society, 2024)
TiO2 is a versatile photo-/electrochemically active material that finds a wide variety of applications in industry and science alike. Its main but often overlooked advantage is the abundance of Ti in nature, as it is the 9th most commonly found element in the Earth’s crust. Despite some drawbacks (e.g., large band gap) that limit its light conversion efficiency in comparison to some other materials, it is particularly inert in corrosive media, and its properties can be modified by various means. In this study TiO2 films are synthesized by an anodization-like procedure called plasma electrolytic oxidation. By varying synthesis conditions different morphologies and structures are obtained. Moreover, successful heterostructuring is achieved by adding a copper precursor into the solution. The TiO2/CuxO films are comprehensively characterized for their structural, optical, and photoelectrochemical properties. Interpretation of XPS and XANES spectra suggest that the content of Cu2+ increases in relation to the maximum voltage reached during synthesis. The UV-vis absorption was also found to display a distinct Cu2+ absorption footprint, as well as lower optical band gap values for the heterostructures. A comprehensive photoelectrochemical characterization for water splitting in 1 M KOH reveals that the TiO2/CuxO films exhibit improved activity overall. © 2024 The Author(s). Published on behalf of The Electrochemical Society by IOP Publishing Limited. --//-- This is an open-access article R. Levinas and V. Pakstas and A. Selskis and T. Murauskas and R. Viter and A. Anspoks and I. Pudza and A. Kuzmin and L. Tamasauskaite-Tamasiunaite and H. Cesiulis and E. Norkus; Plasma Electrolytic Oxidation Synthesis of Heterostructured TiO2/CuxO Films for Photoelectrochemical Water Splitting Applications; Journal of The Electrochemical Society, 171 (3); 036501, 2024, Journal of the Electrochemical, doi: 10.1149/1945-7111/ad2ba7 published under the CC BY 4.0 licence.
We acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Parts of this research were carried out at PETRA III and we would like to thank Dr Edmund Welter for his assistance in using the P65 beamline. Beamtime was allocated for proposal I-20220930 EC.Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART²
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Anodic Films; Oxidation; Photoelectrochemistry; Plasma; Thin film growth; Titanium oxide; Water splitting